Pengaruh Decanter Solid dan Pupuk NPK terhadap Peningkatan Pertumbuhan Bibit Kelapa Sawit di Main Nursery - Imam Prasetyo; Sri Manu Rohmiyati; Herry Wirianata (Program Studi Agroteknologi INSTIPER, 2023)
Solid decanter is one of the by-products from palm oil mills, whichÂ have not used as much as empty fruit bunches. The purpose of this study was to determine the effect of solid decanter as a mixture of nursery media and NPK doses on the increament growth of oil palm seedlings in the main nursery (MN). This study used a factorial experiment with a completely randomized design. Solid mixture: soil consisting of: 0: 1, 1: 3; 1:2, and 1 : 1 (volume/volume) of decanter solid. NPK fertilizer rate consist of: 23, 46, 69, and 92 g/seedling. There were 16 treatment combinations with four replications. The results showed that mixing solid in the media resulted inÂ the growth increament of oil palm seedlings in MN which was the similar as soil media solely. However, the root system of these seedlings is more developed in soil media than in media containing solid decanters. While the difference in NPK rates results in the similar growth increament of oil palm seedlings.